2014
DOI: 10.1111/1574-6941.12390
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of extradiol dioxygenases in aromatic-degrading microbial community explored using both culture-dependent and culture-independent approaches

Abstract: Culture-dependent and culture-independent approaches were used for extensive retrieval of the extradiol dioxygenase (EDO) gene from the environment to investigate the relationship between the EDO genes from isolated bacteria and the metagenomic EDO genes from which they were isolated. In our previous study, we identified 91 fosmid clones showing EDO enzyme activity using a metagenomic approach. In the present study, we classified all these metagenome-derived EDOs and newly isolated 88 phenol-utilizing bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In group II, six relative proteins were from sequenced microbial genomes, and thus none of them was characterized; while the C23O in Pseudomona s sp. G67 was just verified its expression activity on the gene level 39 . The two C23Os in our study were characterized and thus could be the representative of this new group.…”
Section: Discussionmentioning
confidence: 99%
“…In group II, six relative proteins were from sequenced microbial genomes, and thus none of them was characterized; while the C23O in Pseudomona s sp. G67 was just verified its expression activity on the gene level 39 . The two C23Os in our study were characterized and thus could be the representative of this new group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to type I Edos, type II Edos have been less well characterized, have fewer available sequences, and have not been previously identified in metagenomic functional analysis. This has been attributed to their presumed scarcity in the environment (41). However, the present analysis revealed that most of the clones encoding type II Edos (UPO51, UPO64, and UPO67) were detected using 2,3-DHB and had very low relative activities with catechol.…”
Section: Discussionmentioning
confidence: 53%
“…The screening using 2,3-DHBP as an indicator resulted in 2.5-foldmore positive clones than the screening on the same number of colonies using catechol (44 versus 17). This resulted in the iden- tification of only 16 edo genes using catechol, compared to the 27 genes that were identified using 2,3-DHBP (6 genes were identified with both substrates [ Table 1]), which suggests that many of the enzymes in the current sample are not sufficiently active toward catechol to enable detection; therefore, although catechol has been the most common substrate used to detect Edo activity (15,16,40,41), it should not be the indicator of choice for its functional detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthocleavage , also known as the β-ketoadipate pathway, is between two hydroxyl groups and catalyzed by intradiol-type dioxygenases using Fe(II) as cofactor (Guzik et al 2013 ). Meta-cleavage is on the carbon-carbon bond adjacent to the hydroxyl groups through the formation of an α-keto-lactone intermediate, catalyzed by extradiol-type dioxygenases, using Fe(III) as cofactor (Suenaga et al 2014 ). Ortho cleavage of the catechol ring is catalyzed by catechol 1,2-dioxygenase to cis,cis-muconate; catechol meta-cleavage is catalyzed by catechol 2,3-dioxygenase to 2-hydroxy-muconic semialdehyde.…”
Section: Aromatic Hydrocarbon Biodegradation Under Aerobic Conditionsmentioning
confidence: 99%